Increasing deposition efficiency of N-3 LC-PUFA in Altlantic Salmon smolt using high DHA and ALA oils - Nuez Ortin, W; Christopher Carter; Nichols, PD; Richard Wilson (2015)
Introduction Effective fish oil (FO) replacement strategies in Atlantic salmon require enhanced retention efficiency of omega-3 long-chain (≥C20) polyunsaturated fatty acids (n-3 LC-PUFA). This can be achieved via reduced β-oxidation of n-3 LC-PUFA or via promoted bioconversion from shorter chain and less unsaturated precursors. Both mechanisms can potentially be induced by balancing the dietary supply of specific fatty acids, particularly docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and alpha-linolenic acid (ALA) (Stubhaug et al., 2007, Codabaccus et al., 2012). The present study evaluated whether feeding a diet with a higher DHA:EPA ratio and higher ALA content than from a FO based diet would improve retention efficiency of n-3 LC-PUFA in Atlantic salmon smolt. Recent advances in proteomics were used to attempt to gain further insight into the regulatory mechanisms governing lipid metabolism in Atlantic salmon. Materials and methods Atlantic salmon smolt (mean initial weight of 100 g) were acclimatized and subsequently randomly allocated in 12 × 500 L tanks at a stocking density of 24 fish tank per tank. Over 89 days, fish were fed three experimental diets (n=4); a 100% fish oil based diet (100FO), a commercial like oil blend containing 20% FO and 80% poultry oil (20FO80PO), and a blend of 60% tuna oil and 40% flaxseed oil (60TO40FX). The fatty acid profile of 60TO40FX reflected that of DHA-enriched land plant oil (Petrie et al., 2014). Compared to 100FO and 20FO80PO diets, the 60TO40FX diet contained a higher DHA:EPA ratio (0.9, 1.0 and 3.4) and ALA content (2.1, 3.8, 38.3 mg per g DM). Daily feed intake, weight gain and digestibility were measured as previously described (Codabaccus et al., 2012). Shotgun proteomic analysis of liver tissue is underway. Results Over the duration of the growth trial, fish had an average 2.2 fold increase in body weight. Feed intake, final fish weight, and total lipid concentration in muscle and liver were not significantly affected by oil composition. The content ...